2017
DOI: 10.3389/fpls.2017.00708
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Accumulation of Secondary Metabolites in Perilla as Affected by Photosynthetic Photon Flux Density and Electrical Conductivity of the Nutrient Solution

Abstract: The global demand for medicinal plants is increasing. The quality of plants grown outdoors, however, is difficult to control. Myriad environmental factors influence plant growth and directly impact biosynthetic pathways, thus affecting the secondary metabolism of bioactive compounds. Plant factories use artificial lighting to increase the quality of medicinal plants and stabilize production. Photosynthetic photon flux density (PPFD) and electrical conductivity (EC) of nutrient solutions are two important facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 44 publications
7
60
1
Order By: Relevance
“…Extraction was conducted according to the Japanese Pharmacopoeia (Ministry of Health, Labour, & Welfare of Japan, ) and a method described in a previous article (Lu et al, ) with modifications. A sample, ca 20 mg of a dry leaf and ca 150 mg of a fresh leaf, was weighed accurately and transferred to a 1.5‐ml tube.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction was conducted according to the Japanese Pharmacopoeia (Ministry of Health, Labour, & Welfare of Japan, ) and a method described in a previous article (Lu et al, ) with modifications. A sample, ca 20 mg of a dry leaf and ca 150 mg of a fresh leaf, was weighed accurately and transferred to a 1.5‐ml tube.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction was conducted according to the Japanese Pharmacopoeia (Ministry of Health, Labour, & Welfare of Japan, 2017) and a method described in a previous article (Lu et al, 2017) with modifications.…”
Section: Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…acuta Kudo f. crispa Makino, 0657-79TS, National Institute of Biomedical Innovation, Osaka, Japan) seeds were sown in rockwool cubes (125 cm 3 ) in a cultivation room. e LI was set to 150 µmol·m −2 ·s −1 (the unit of µmol·m −2 ·s −1 represents photosynthetic photon flux density on the surface of cultivation containers) with a photoperiod of 16 h per day provided by cool white fluorescent lamps (FHF32 EX-N-H, Panasonic, Co., Ltd., Japan), and the plants were irrigated with a nutrient solution (Otsuka hydroponic composition, OAT Agrio Co., Ltd., Tokyo, Japan) (Otsuka formula as described by Lu et al [16]). e electrical conductivity (EC) and pH of the nutrient solution were adjusted to 1.2 dS·m −1 and 6.0, respectively.…”
Section: Perilla Materials and Growth Conditionsmentioning
confidence: 99%
“…In a previous study, we found that rosmarinic acid (RA), a major phenylpropanoid compound in herbs of Lamiaceae family, is highly increased in P. frutescens grown under uptake stress created by a nutrient-limited condition combined with high light intensity (LI) in plant factories, while maintaining a constant concentration of perillaldehyde (PA), a main terpenoid found in perilla essential oils [16]. Given the differences that exist between terpenoids and phenylpropanoids with respect to biosynthetic pathways and accumulation, there likely are no synchronous increases in PA and RA.…”
Section: Introductionmentioning
confidence: 99%